Variáveis preditivas de prestações de contas irregulares em convênios realizados pelo Estado do Ceará - Albuquerque, Carlos Ernesto Saboia de (2024)
This research investigates which variables are correlated with irregular financial statements in agreements made by the state of Ceará. The variables used are related to the body granting the resources, the receiving entity and the instrument itself, in addition to economic and electoral variables. In this sense, logit regression models were estimated using data from the 6,396 agreements, initiated between 2015 and 2022, provided by the General Comptroller and Ombudsman of the State of Ceará, where the data is managed and stored. The results indicate that variables linked to the state and federal economies, the characteristics of grantors and receivers, elections and the complexity of the object executed impact the regularity of transferred resources. It is mentioned that the Industrial Production Index and the age of the receiver have a positive influence on the approval of accounts for these financial transfer instruments. The variable basic interest rates (SELIC), the occurrence of municipal elections and the updated value of the agreement demonstrated a negative impact on the regularity of these same accounts.